Stress induces analgesia via orexin 1 receptor-initiated endocannabinoid/CB1 signaling in the mouse periaqueductal gray. (June 2016) - Lee, Hsin-Jung; Chang, Lu-Yang; Ho, Yu-Cheng; Teng, Shu-Fang; Hwang, Ling-Ling; Mackie, Ken; Chiou, Lih-Chu
Abstract: The orexin system consists of orexin A/hypocretin 1 and orexin B/hypocretin 2, and OX1 and OX2 receptors. Our previous electrophysiological study showed that orexin A in the rat ventrolateral periaqueductal gray (vlPAG) induced antinociception via an OX1 receptor-initiated and endocannabinoid-mediated disinhibition mechanism. Here, we further characterized antinociceptive effects of orexins in the mouse vlPAG and investigated whether this mechanism in the vlPAG can contribute to stress-induced analgesia (SIA) in mice. Intra-vlPAG ( i.pag. ) microinjection of orexin A in the mouse vlPAG increased the hot-plate latency. This effect was mimicked by i.pag. injection of WIN 55, 212-2, a CB1 agonist, and antagonized by i.pag. injection of the antagonist of OX1 (SB 334867) or CB1 (AM 251), but not OX2 (TCS-OX2-29) or opioid (naloxone), receptors. [Ala 11, D-Leu 15 ]-orexin B ( i.pag. ), an OX2 selective agonist, also induced antinociception in a manner blocked by i.pag. injection of TCS-OX2-29, but not SB 334867 or AM 251. Mice receiving restraint stress for 30 min showed significantly longer hot-plate latency, more c-Fos-expressing orexin neurons in the lateral hypothalamus and higher orexin levels in the vlPAG than unrestrained mice. Restraint SIA in mice was prevented by i.pag. or intraperitoneal injection of SB 334867 or AM 251, but not TCS-OX2-29 or naloxone. These results suggest that during stress, hypothalamic orexin neurons are activated, releasing orexins into the vlPAG to induce analgesia, possibly via the OX1 receptor-initiated, endocannabinoid-mediated disinhibition mechanism previously reported. Although activating either OX1 or OX2 receptors in the vlPAG can lead to antinociception, only OX1 receptor-initiated antinociception is endocannabinoid-dependent. Highlights: Orexins induce analgesia via endocannabinoids in the periaqueductal gray. Restraint stress activates hypothalamic orexin neurons, leading to analgesia. Stress-induced analgesia via OX1 and CB1 receptors in the periaqueductal gray. Activating OX2 receptors in the periaqueductal gray also induces analgesia.